A calibration procedure for analyzing stock price dynamics in an agent-based framework - Maria Cristina Recchioni; Gabriele Tedeschi; Mauro Gallegati (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
In this paper we introduce a calibration procedure for validating of agent based models. Starting from the well-known financial model of Brock and Hommes 1998, we show how an appropriate calibration enables the model to describe price time series. We formulate the calibration problem as a nonlinear constrained optimization that can be solved numerically via a gradient-based method. The calibration results show that the simplest version of the Brock and Hommes model, with two trader types, fundamentalists and trend-followers, replicates nicely the price series of four different markets indices: the S&P 500, the Euro Stoxx 50, the Nikkei 225 and the CSI 300. We show how the parameter values of the calibrated model are important in interpret- ing the trader behavior in the different markets investigated. These parameters are then used for price forecasting. To further improve the forecasting, we modify our calibration approach by increasing the trader information set. Finally, we show how this new approach improves the model's ability to predict market prices.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C53; C63; G17; 330; Calibration; Validation; Forecasting; Agent-based models; Asset pricing; Heterogeneous beliefs